A systematic review and net meta-analysis of the effects of different warm-up methods on the acute effects of lower limb explosive strength - Li, F. Y.; Guo, C. G.; Li, H. S.; Xu, H. R.; Sun. P. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Objective To evaluate the effects of different warm-up methods on the acute effect of lower limb explosive strength with the help of a reticulated meta-analysis system and to track the optimal method.